2. Yacimientos Uraníferos. 2. Los minerales de uranio - Toubes, Roberto O. (Comisión Nacional de Energía Atómica; Argentina, 1978)
Fil: Toubes, Roberto O. Comisión Nacional de Energía Atómica; Argentina